Implementing the African Continental Free Trade Agreement (AfCFTA): policies, regulations, laws and institutions required for development - Nagu, Yakubu (Department of Commercial Law, 2024)
On 26 May 2013 at the 21st Ordinary Assembly of the African Union's Assembly, African heads of state and governments adopted a solemn declaration for the continent's development. This prompted, in 2015, the official launch of a 50-year blueprint (i.e. Agenda 2063) for the re-creation of the region through a people-driven process into one that is integrated, prosperous and defined by inclusive growth and sustainable development. This blueprint has 15 flagship projects for effectuating the aim of continental growth, transformation, and development. One of these flagship projects is the African Continental Free Trade Area (AfCFTA), Africa's most ambitious attempt at integration and development since the formation of the African Union, and the subject of this research. The AfCFTA is an African Union member-state driven free trade area, founded on theories of trade, and driven by Pan-African values that promise an endogenous pathway to inclusive and sustainable development. The initiative, once fully operational, will have the effect of integrating the continent for the first time under one regime of liberalisation that covers goods, services, intellectual property, investment, competition, and digital trade, among others. It is submitted, however, that trade integration alone may not provide enough stimulus for the holistic development that the region deeply requires. Development, imposes (in addition to increasing trade by operationalising the AfCFTA) an imperative for building regulatory and institutional capacity and (where necessary) reforming the trade governance processes in the state parties. It is against this background that this study probes into the implementation of the AfCFTA in the context of select case studies; Nigeria, Kenya and Ethiopia. The study combined doctrinal research with empirical methods that utilised semi-structured interviews with public and private sector stakeholders from the three countries. The thesis is structured into two parts. The first one outlines the theoretical and analytical framework as a means of situating the AfCFTA in the broader conversation on development, international trade, and regional integration whilst also reflecting it as a unique and Pan-African expression of same. The second examines the mentioned case studies through the lens of the Analytical Law and Developmental Integration Model (ALDIM) developed by the researcher. The study found that a developmental implementation of the AfCFTA by the three countries that have been selected as case studies would require responses ranging from a shift in development thinking and the creation of value-driven trade policy frameworks to more pragmatic steps such as the creation of institutional mechanisms for cohesive trade policy formulation and governance, the strengthening of existing institutions, and the institutionalisation of collaboration for a more inclusive trade policy governance. Ultimately, the study advances projections on how regional integration initiatives could yield development outcomes in domestic settings in the context of African states, thereby affirming the influence of trade as an agent for modernisation and the positive alteration of governance processes.